Application of Peat-B as Additives in Waterproofing Liner Material - Nur Alya Syazwanie binti Suhaimi (Recent Trends in Civil Engineering and Built Environment, 2021)
Wet and damp conditions will cause building damage to become faster and will increase maintenance costs each year. The goal of this study was to produce an effective waterproof coating capable of solving the problem of damage caused by water or moisture. This study uses a mixture of clay as the main material and PEATB as an additive to produce a waterproof layer that can be used in any construction application such as building and road construction. PEAT-B is a mixture of peat particles and bentonite. Different percentages of mixed materials will be produced to study the appropriate percentage to be used as a waterproof layer. Tests such as water permeability (Falling head), water absorption and Self-healing are used to test the effectiveness of the waterproof layer mixture. The results showed that with the increase in the percentage of bentonite in the PEAT-B mixture showed good results. The results of the study showed that B25 with mixtures such as Water (20%), Clay (80%), Peat Particles (10%) and Bentonite (25%) had produced the best results among other mixtures. By producing this waterproof layer, then the problem of leakage and water seepage on certain building structures such as concrete walls or roofs or roads will be avoided.